2009
DOI: 10.1002/btpr.254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different magnetites on properties of magnetic Pseudomonas aeruginosa immobilizates used for biosurfactant production

Abstract: During the last decades, whole-cell immobilization has been used successfully in many bioprocesses. In particular, it is aimed at implementing continuous production processes, reaching higher production rates, and reusing the biocatalyst. In some cases, effective retention of immobilizates in the bioprocess is not feasible by membranes or sieves due to pore plugging or undesired losses of immobilizates. In the present publication, it is reported about the investigation of magnetic immobilizates of Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…5b) to external fields, which implies usefulness for various bioapplications including magnetically assisted cell separation, 36 drug delivery 37 and removal of micro-organisms. 38 The size of our products is comparable to commercially available magnetic nanoparticles with silica surface, such as SiMAG (0.5 mm to 1 mm size, Chemicell), BcMagÔ (1 mm size, Bioclone) and MagPrep Ò (0.1mm size, Merck), having $26, 39 40 40 and 88 emu/g composite, 41 respectively, which are used for magnetic bioseparation.…”
Section: Resultsmentioning
confidence: 82%
“…5b) to external fields, which implies usefulness for various bioapplications including magnetically assisted cell separation, 36 drug delivery 37 and removal of micro-organisms. 38 The size of our products is comparable to commercially available magnetic nanoparticles with silica surface, such as SiMAG (0.5 mm to 1 mm size, Chemicell), BcMagÔ (1 mm size, Bioclone) and MagPrep Ò (0.1mm size, Merck), having $26, 39 40 40 and 88 emu/g composite, 41 respectively, which are used for magnetic bioseparation.…”
Section: Resultsmentioning
confidence: 82%
“…The produced immobilizates had a particle size distribution ranging from about 30 μm to 640 μm (for 95% of beads) with a medium volume‐related particle size of ∼240 μm ( x AV , 50 ). The initial specific saturation magnetization of the humid immobilizates was ∼5 A m 2 kg −1 and, hence, more than sufficient for magnetic separation in a high‐gradient magnetic separator 40…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of Pseudomonas bacteria and iron ions from magnetic nanoparticles has been studied by several research teams focused on the magnetite nanoparticle antimicrobial features [18][19][20], while others developed some biotechnological applications. Liu et al(2009) have proposed a method for targeting bacteria from clinical samples based on the interaction between the galactophilic lecithin from P. aeruginosa membrane receptors and the magnetic nanoparticles coated with phosphoproteic containing Galα(1-4)Gal units [21], while Heyd et al(2009) reported on the investigation of magnetic immobilizates of P. aeruginosa on magnetite for the application in continuous biosurfactant production of rhamnolipids [22]. Pseudomonas delafieldii labeled with magnetic Fe 3 O 4 /ammonium oleate nanoparticles and immobilized by external magnetic field was found able of greater desulfurization activity than free cells or cells immobilized on celite (Shan et al, 2005) [23].…”
Section: Introductionmentioning
confidence: 99%